Protective Effects of Zingiber Officianale on Isoniazid induced Hepatotoxicity in Albino Rats: A Histomorphological Study - Muhammad Hussain Siddiqui; Naheed Khan; Naseem Ahmed; Tahir Hussain; Naheed AKhtar; Syeda Zain (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: Tuberculosis (TB) continues to exist as a fatal, rampant disease in most developing countries of the world, including Pakistan. Isoniazid (INH) is an effective drug of choice for the disease, but poses a significant risk of hepatotoxicity. Studying the ability of natural supplements like Ginger to counter the hepatotoxicity of INH may lead to a breakthrough in Tuberculosis treatment. The study aimed to investigate the protective effect of Zingiber officinale (Ginger) on isoniazid induced hepatotoxicity in albino rats as manifested by histomorphological changes.  Methods: An experimental study was conducted over a period of six months on 40 adult albino rats .  The rats were divided by random sampling into four groups of ten each: Control group, Ginger group, INH group and INH+Ginger group. Rat livers were dissected and studied under light microscope for recording histomorphological changes. Data was analysed using IBM-SPSS version 23.0.  Results: None of the specimens of the Control or Ginger groups (0%) showed any features of alteration in liver architecture. Periportal hepatitis was moderate in the INH group (90%) and mild in INH+Ginger group (90%). Confluent necrosis and focal and portal inflammation were present in both INH and INH+Ginger groups to varying degrees. Fibrosis was visible in 100% of the INH group versus only 10% of INH+Ginger group. Steatosis was found in 80% of the INH group versus only 10% of INH+Ginger group. All findings showed significant association between groups (p<0.001).  Conclusion: Ginger has hepato-protective effects against INH-induced hepatotoxicity in male albino rats.